Temporal-spatially transformed synthesis and formation mechanism of gold bellflowers. Issue 14 (3rd November 2015) - Lin, Jing; Zhang, Molly G.; Tang, Yuxia; Wen, Bronte; Hu, Hao; Song, Jibing; Liu, Yijing; Huang, Peng; Chen, Xiaoyuan
Abstract : We synthesized gold nanourchins, gold microspheres, and gold bellflowers in monophasic, biphasic, and triphasic systems, respectively, and investigated their formation mechanisms. Abstract : Anisotropic gold nanostructures with unique plasmonic properties, specifically the strong absorption of light in the near-infrared region (650–900 nm) due to the excitation of plasmon oscillations, have been widely employed as photothermal conversion agents (PTCAs) for cancer photothermal therapy (PTT). However, the reported PTCAs show suboptimal photothermal conversion efficiency ( η ), even gold nanocages ( η = 63%), which limits their biomedical applications. Herein, we fabricated gold bellflowers (GBFs) with an ultrahigh photothermal conversion efficiency ( η = 74%) via a novel liquid/liquid/gas triphasic interface system, using chloroauric acid as a gold source, and o -phenetidine as a reducing agent. The well-defined GBFs with multiple-branched petals show adjustable localized surface plasmon resonance (LSPR) from 760 to 1100 nm by tuning the petal length and circular bottom diameter. Originating from the monophasic and biphasic systems used in the creation of gold nanourchins (GNUs) and gold microspheres (GMPs) respectively, the triphasic interface system successfully produced GBFs. The possible formation mechanisms of GNUs, GMPs, and GBFs in the different systems were also investigated and discussed. We found that the formation mechanism of GNUs and GBFs followed classical crystallization, while the formation of GMPs followed non-classical crystallization.